Transition shock among nursing students during clinical practice: a scoping review protocol - Miao Zhang; Xue-Li Jia; Shuang-Shuang Ren; Yang-Yang Huang; Pei-Li Shi; Yu Mi; Gui-Yue Zhu (BMJ Open)
Introduction Transition shock is a very common negative clinical practice experience for nursing students, which not only makes the adaptation to clinical practice difficult but also influences the smooth transition from nursing students to registered nurses and eventually could lead them to leave the nursing field. Therefore, transition shock of nursing students deserves attention. Recently, there has been a notable increase in research dedicated to transition shock experienced by nursing students. However, the overview of research done on this topic remains unclear. Therefore, we will conduct a scoping review to summarise assessment tools, influencing factors, the impacts and intervention strategies of transition shock among nursing students and identify knowledge gaps in this field to guide further research.Methods and analysis We will follow the Joanna Briggs Institute scoping review guidelines to conduct this scoping review. A comprehensive literature search will be conducted through 12 databases and grey literature sources. The search period will be restricted from May 2009 to December 2024, and this review will only incorporate publications in Chinese or English. Two researchers will independently screen the literature according to inclusion criteria, and then conduct data extraction. Any differences arising between the two researchers will be addressed by engaging in discussion with a third researcher. We will collate, summarise and analyse the extracted data and subsequently present the results by means of figures, tables and descriptive narratives. This review will be reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews reporting checklist.Ethics and dissemination As this review does not involve patients or the public, there is no need for ethical approval. The results of this scoping review will be disseminated by means of conference presentations and publication in a peer-reviewed academic journal.Registration Open Science Framework (https://osf.io/2r6jn/).